2022
DOI: 10.1021/acsami.2c03520
|View full text |Cite
|
Sign up to set email alerts
|

Nonmonotonic Relationship between the Oxidation State of Graphene-Based Materials and Its Cell Membrane Damage Effects

Abstract: With the rapid development of carbon-based two-dimensional nanomaterials in biomedical applications, growing concern has emerged regarding their biocompatibility and especially their interactions with cell membranes. Our experimental studies found that the oxidation state, as one of the most important chemical parameters of graphene derivatives, regulates the hemolysis effect on human red blood cells in a nonmonotonic manner. Scanning electron microscopy and optical microscopy observations suggested that graph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Although the surface of GO also contains C–O–C, −OH, −COOH, and CO groups, a large area of unoxidized regions (sp 2 domain) remains as illustrated by the characterizations using ultra-high-resolution transmission electron microscopy in several previous literature studies. Specifically, Gómez-Navarro et al reported that the unoxidized regions of GO can reach ∼60%. Therefore, the strong direct vdW attractions coordinated with hydrophobic interactions between those unoxidized regions with the lipid hydrophobic tails can still destroy the cell membrane. , In addition, the keen-edged corners of GO nanosheets should also facilitate their cell membrane damage effects, promoting hemolytic activity (Figure S4). The important role of these sharp corner sites in assisting GO nanosheets to penetrate cell membranes had been thoroughly illustrated previously by combining multiscale modeling and imaging experiments …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the surface of GO also contains C–O–C, −OH, −COOH, and CO groups, a large area of unoxidized regions (sp 2 domain) remains as illustrated by the characterizations using ultra-high-resolution transmission electron microscopy in several previous literature studies. Specifically, Gómez-Navarro et al reported that the unoxidized regions of GO can reach ∼60%. Therefore, the strong direct vdW attractions coordinated with hydrophobic interactions between those unoxidized regions with the lipid hydrophobic tails can still destroy the cell membrane. , In addition, the keen-edged corners of GO nanosheets should also facilitate their cell membrane damage effects, promoting hemolytic activity (Figure S4). The important role of these sharp corner sites in assisting GO nanosheets to penetrate cell membranes had been thoroughly illustrated previously by combining multiscale modeling and imaging experiments …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the strong direct vdW attractions coordinated with hydrophobic interactions between those unoxidized regions with the lipid hydrophobic tails can still destroy the cell membrane. 69 , 76 In addition, the keen-edged corners of GO nanosheets should also facilitate their cell membrane damage effects, promoting hemolytic activity ( Figure S4 ). The important role of these sharp corner sites in assisting GO nanosheets to penetrate cell membranes had been thoroughly illustrated previously by combining multiscale modeling and imaging experiments.…”
Section: Resultsmentioning
confidence: 99%
“…MD simulations revealed that the endocytosis of graphene occurred via flat vesiculation and graphene self-rotation (Figure F) . Graphene suspended outside the cell membrane can destructively extract numerous lipids from the membrane and induce lipid depletion, membrane damage, and finally cytotoxicity (Figure G). These distinctive pathways of graphene interactions with cell membrane suggest that the NM–cell membrane interactions are strongly dependent on the NM’s physicochemical properties and the microenvironment, as will be discussed in the following section.…”
Section: Elucidating Nanotoxicity Mechanisms By Molecular Simulationsmentioning
confidence: 98%